2019
DOI: 10.1002/ldr.3396
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the extent and distribution of urban land cover in the Democratic People's Republic of Korea (North Korea) between 1987 and 2010

Abstract: Largely due to data unavailability, the spatial pattern of urban growth in North Korea has been rarely studied. This study explored urban changes in North Korea and provided their plausible causes. The present study used satellite‐based land cover data sets produced by the government of South Korea to examine the extent and distribution of urban land cover in North Korea between the late 1980s (1987–1989) and late 2000s (2008–2010) at the municipal level. The urban expansion intensity index (UEII) was calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…It spatially visualized multiple types of land covers of Kaesong based on the Korean Multi-Purpose Satellite but with a broader geographical scope, compared to Kim et al [20]. While these two studies demonstrated only the land categories of Kaesong for each year, Kang et al [16] analyzed the change of Built areas in Kaesong, along with the other nine large cities in North Korea. According to the authors, Kaesong's urbanization was more intensive in the 1980s-1990s than the 1990s-2000s, only analyzing LUCCs during the South-North division.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It spatially visualized multiple types of land covers of Kaesong based on the Korean Multi-Purpose Satellite but with a broader geographical scope, compared to Kim et al [20]. While these two studies demonstrated only the land categories of Kaesong for each year, Kang et al [16] analyzed the change of Built areas in Kaesong, along with the other nine large cities in North Korea. According to the authors, Kaesong's urbanization was more intensive in the 1980s-1990s than the 1990s-2000s, only analyzing LUCCs during the South-North division.…”
Section: Discussionmentioning
confidence: 99%
“…Among Asian urban areas under centralized socialist regimes, LUCCs in cities and border regions of mainland China and Vietnam have been studied extensively via remote sensing data [7][8][9][10][11][12][13][14][15]. However, much less is known about LUCCs in North Korea (i.e., Democratic People's Republic of Korea) or in areas along the inner border of South and North Korea [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The UEII method was used to analyze the characteristics of land use morphology [38,47,48]. Shenghe et al [47] analyzed the urban expansion speed of Beijing in China by using UEII.…”
Section: Discussionmentioning
confidence: 99%
“…The average yearly proportion of a newly enlarged urban area to the total area is the urban expansion intensity index (UEII) for a spatial unit [38]. Urban expansion can occur in different directions in every urban area depending on its driving factors, including road networks, population density, slope, economy, etc.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation